Primerjava dendrokronoloških raziskovanj z ocenjevanjem prirastka na gozdarskih raziskovalnih ploskvah - Hladnik, David (Gozdarski vestnik, 2021)
We compared the results of dendrochronological research of mature spruce trees from the stand canopy with the assessment of radial increment on the study plots in spruce stands on Pokljuka. In the comparison, we use raw measurement data (age trend was not removed) from dendrochronological analysis of radial growth of spruce trees and compare them with the findings on radial growth on the research plots. On the research plots established 60 years ago, we assessed DBH increments, growing stocks, and volume increments in individual periods using serial tree diameter measurements. Variability in average DBH increment in the highest DBH classes on the research plots was comparable to assessments for dominant trees analyzed in the dendrochronological analysis. The data from the dendrochronological analysis provide a good baseline and important support for assessing developmental dynamics in forest stands and evaluating changes over 5- or 10-year periods of continuous forest inventories.
Keywords: DBH increment; debelinski prirastek; dendrochronological analysis; dendrokronološka analiza; forest inventories; gozdne inventure; smreka; spruce